MACHINING MODEL OF TI-6AL-4V TITANIUM ALLOY USINGFEM SIMULATION - Amran, M.M.A., Hadzley, M.M.A., Raja Izamshah, R.A., (Journal of Advanced Manufacturing Technology (JAMT), 2014)
This paperpresents a machining modelof Ti-6Al-4V titanium alloy using finite element method (FEM) simulation. The constitutive Johnson–Cook material flow stress was employed to predict material plasticity, chip morphology, cutting forces and stress distribution. Comparative analysis for both simulation and experimental data were carried out. The simulated results show that workpiece material flow around the cutting edge of the tool and deposited themselves to form a continuous curl chip formation. The stress distribution generated in the shearing plane during steady state conditions and the residual stress is formed beneath the machined surface.The cuttingforces were essentially constant across the range of cutting speeds. This agreedwith the trend from the experimental trials.